2017
DOI: 10.3748/wjg.v23.i18.3374
|View full text |Cite
|
Sign up to set email alerts
|

Severe esophageal injury after radiofrequency ablation - a deadly complication

Abstract: Various degrees of esophageal injury have been described after radiofrequency ablation performed for treatment of atrial fibrillation. The main mechanism of injury is thermal and may lead to a range of esophageal mucosal changes, some clinically insignificant, however when deep ulceration occurs, this may be further complicated by perforation and mediastinitis, a rare but life threatening sequelae. We present a case of a severe esophageal injury leading to mediastinitis, with interesting endoscopic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
9
0
3
Order By: Relevance
“…If a double heat exposure is applied, this effect intensifies, further damaging the surrounding tissues. This continued destruction, while positive in diseased tissue, is difficult to monitor and control and may result in a high degree of heat based complications, such as hematoma and neoplasia [48][49][50][51][52]. The addition of the freezing step after heating could theoretically remove residual heat load remaining following hyperthermia, potentially reducing the risk of collateral damage and unwanted complications to surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…If a double heat exposure is applied, this effect intensifies, further damaging the surrounding tissues. This continued destruction, while positive in diseased tissue, is difficult to monitor and control and may result in a high degree of heat based complications, such as hematoma and neoplasia [48][49][50][51][52]. The addition of the freezing step after heating could theoretically remove residual heat load remaining following hyperthermia, potentially reducing the risk of collateral damage and unwanted complications to surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why RFA delivered in the left atrium can cause thermal damage and perforation of the esophagus without fistula formation through the posterior left atrium. The fistula appears to start first in the esophagus and progress toward the left atrium and pericardium ( 6 , 7 ). Furthermore, it is possible that patients with esophagopericardial fistula are at risk of progression to atrioesophageal fistula, as demonstrated by Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…When reviewing the literature regarding esophago-mediastinal fistulous formation, we found 23 cases of esophageal perforation without a fistulous communication with the left atrium. 6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Only one of the 23 cases was screened early after ablation having a normal esophagoscopy, before developing perforation two weeks later 4 (Table 1). Park et al 4 also reported that another patient, who likely died of esophageal-atrial fistula, had a normal endoscopy on the second day after the procedure.…”
Section: Esophagus Perforation and Fistula Developmentmentioning
confidence: 99%
“…In that light, we report our patient who developed esophago‐pericardial fistula three weeks after radiofrequency pulmonary vein isolation, who had a normal esophagoscopy after the procedure. When reviewing the literature regarding esophago‐mediastinal fistulous formation, we found 23 cases of esophageal perforation without a fistulous communication with the left atrium 6,7,11–26 . Only one of the 23 cases was screened early after ablation having a normal esophagoscopy, before developing perforation two weeks later 4 (Table 1).…”
Section: Esophagus Perforation and Fistula Developmentmentioning
confidence: 99%